Economic Analysis of Sawnwood Marketing in Isokan Local Government area Osun State, Nigeria - A. R. Falana; F. F. Ojo-Fakuade; A. F. Joseph; F. T. Adelusi; O. O. Oke; M. A. Majolagbe; F. B. Adesokan (Journal of Applied Sciences and Environmental Management, 2023)
Sawnwood is wood that has been produced either by sawing lengthways or by a profile-chipping process and is greater than 6 millimetres. The study evaluates the economic analysis of sawnwood marketing in Isokan Local Government area of Osun state Nigeria using appropriate standard methods. The results showed that 67.5% of the respondents were males while 28.3% were females. Most of the respondents (50%) are in their active ages, a large percentage (51.2%) of the respondents got into the business of planks marketing by training and started its runs through bank loans. Eight (8) major wood species: Albizia zygia, Blighia sapida, Ccordia milleni, Gmelina arborea, Milicia excelsa, Nuclea diderrichii, Termilania superba, and Triplochiton scleroxylon were sold in the study area. The constraints faced by the plank market business are unavailability means of transportation, government tariffs, price fluctuation in purchase, scarcity of timber and bad roads. There is significant relationship between the socio economic characteristics and the constraints facing sawnwood marketing in the study area. Results showed that for every $0.0022 invested into the sawn wood business, $0.0055 is returned, this implies that timber marketing business is a worthwhile business. It is thus recommended that there is a need for sawn wood marketers to organize themselves into cooperative groups in order to secure loan and credit facilities from funding agency so as to ease the constraints faced by them to boost their returns.